AgriForScape Model: Optimization of Agricultural Landscape Design in Karawang District as a Pest Control Strategy with an Ecological Approach - Selvianing Tiyas; Wildan Maynardy Wicaksono; Usnil Khotimah; Ali Dzulfigar; Danik Septianingrum; Rahmat Asy’ari; Muhammad Ferdiansyah; Neviaty P Zamani; Rahmat Pramulya; Yudi Setiawan (CELEBES Agricultural, 2024)
Karawang Regency is one of the national rice barns and a major supplier of rice to Jakarta and surrounding areas. However, the productivity of this rice is threatened by the brown planthopper (Nilaparvata lugens) which causes crop failure. The reliance on chemical pesticides to control this pest results in negative impacts on the environment and endangers human health. This caused a decrease in land productivity resulting in the conversion of land use to non-agriculture. This research aims to analyze the conditions and problems of agricultural areas in Karawang Regency and design a strategy for regulating landscape structures in reducing the intensity of pest attacks in Karawang Regency. Optimizing the structure and pattern of agricultural landscapes using the AgriForScape (Agriculture-Forest-Landscape) model can be one of the effective strategies in pest control to increase land productivity by integrating agriculture and forest land covers. Land cover mapping for 2023 and 2000 was conducted using cloud computing, revealing a conversion of 14,000 hectares of rice paddy land over 23 years, leaving 99,713 hectares. AgriForScape focuses on the integration of agriculture and forest conservation to improve ecosystem balance, increase land productivity, and lower the risk of natural disasters. AgriForScape landscape management can be done with several strategies, including the addition of corridors and forest patches as habitat for natural predators of rat pests, and the addition of refugia areas as food sources and natural habitat for insect pest predators. By applying an ecological approach through optimized agricultural landscape design, this strategy aims to reduce pest attack intensity, boost rice productivity, and contribute to food security and climate change mitigation. The findings are expected to advance sustainable agriculture and offer valuable insights for local governments, farmers, and stakeholders seeking environmentally friendly land management solutions.